The political economy of fiscal federalism and the dilemma of constructing a developmental state in Nigeria (2009)
The relationship between federalism and development needs to be investigated in the context of values of governance and state–society relations, especially citizenship. This helps to uplift the discourse on the African state by situating it within the historiography and political economy of federalism. This article explores the institutional and political foundations of the fundamentally distributive orientation of Nigeria’s fiscal federal system: the values that underlie governance and the character of state–society relations expressed in the demarcation of fiscal federalism from citizenship privileges and duties. It argues that a fragmented citizenship sustains predatory rule, which undermines the developmental content of federalism.